Representasi Novel “Dua Garis Biru” karya Lucia Priandarini Dalam teori Feminisme - Nurrohman Salsabilla, Sinta; Lailiyatus Sa’diyah; Agus Hermawan; Saptono Hadi (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
Feminism is a social and political movement aimed at achieving gender equality between women and men. It challenges discrimination and injustices based on gender in society. Literature portrays aesthetic and linguistic beauty, a novel is a narrative prose literary work. The issue of feminism is currently highly popular among readers; through this article, it is hoped that the reality of feminism in the novel "Dua Garis Biru" can be understood. This article employs a qualitative descriptive method relevant to contextual and real phenomena. The research findings highlight the character of Dara, characterized by hard work, responsibility, and resilience. These traits depict liberal feminism, radical feminism, and Marxist feminism realities. Overall, the novel "Dua Garis Biru" represents existential feminism by portraying strong, independent, dominant female characters who bravely defy gender stereotypes and patriarchal social constructions.